Development of Fe-10% (HA/β-Tricalcium Phosphate) Composite via Solid-State Manufacturing Route and Investigation of Material Properties for Biodegradable Implant Applications - Bulutsuz, Asli Gunay; Chrominski, Witold; Bazarnik, Piotr; Bruder, Enrico (WILEY-V C H VERLAG GMBH, 2024)
Day-by-day biodegradable alloys and composites are getting more attention. Besides their competing material properties with traditional permanent implants, their harmless degradation in the body eliminates the need for a second surgery to remove the implant. Beyond other biodegradable materials such as Mg and Zn, Fe is known with high strength with low degradation rate. However there is still need to improve its biocompatibility. Herein, a Fe-based composite is developed via solid-state manufacturing route. 10% HA/beta-TCP is selected as an additive which is a biocompatible ceramic material and the powder mix is ball-milled. Afterward, the powders are consolidated via high-pressure torsion (HPT) with 1-5-10 revolutions at room temperature. Crack-free structures are obtained even after 1 HTP rotation. Fe is in lamellar form around HA-beta TCP particles. With the increase of HPT rotation numbers, lath thickness decreased. After 10 HPT rotations, 24% enhancement in density is observed that points to a more condensed structure. Transmission electron microscopy observations show significant grain refinement after 1 HPT rotation, and Fe grain size remains constant (approximate to 300 nm) up to 10 turns. Ultimate tensile strength increases while degradation rate decreases after 5 HPT rotations. This study provides the potential of enhanced Fe-based biomaterials for thinner and smaller implant designs.
Keywords: biodegradables; composites; high-pressure torsions; milling; IN-VITRO DEGRADATION; HIGH-PRESSURE TORSION; MECHANICAL-PROPERTIES; CORROSION-RESISTANCE; HYDROXYAPATITE COMPOSITES; PURE IRON; FE-PD; ALLOY; BEHAVIOR; BIOCOMPATIBILITY; Materials Science